EFFECT OF CANNA INDICA L. EXTRACT AGAINST CAFFEINE-NICOTINE CO-ADMINISTRATION-INDUCED EXAGGERATION IN TYPE 2 DIABETIC RATS - SUBHASH T, KUMBHAR; HEMANT D, UNE; DAYANAND M, KANNUR; SHRINIWAS P, PATIL (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was designed to evaluate the protective effect of Canna indica L. extract against caffeine-nicotine administration-induced type 2 diabetes exaggeration in rats. Methods: A study was conducted for three weeks in four rat groups (n=6); viz. type 2 diabetic control group, a caffeine-nicotine diabetic control group (20mg/kg, 0.4mg/kg, ip twice daily), and Canna indica L. extract and caffeine-nicotine treatment group and standard drug treated caffeine-nicotine diabetic group (Glibencamide, 5mg/kg, once daily). Type 2 diabetes was induced by two weeks high fatty diet and a single dose streptozotocin (50mg/kg, ip) on 1th day of the study in all groups. Blood and urine samples were collected every week for serum biochemical analysis. Results: Results of extract treatment and standard drug treatment were compared with untreated caffeine-nicotine co-administration group. Difference in each relevant serum parameter was analyzed through ANOVA and Dunett's t test. Extract treated caffeine-nicotine-diabetic group showed about 150-200mg/dL (p<0.001) reduction in the serum glucose than untreated caffeine-nicotine-diabetic control group. Extract treatment reduces serum glucose by 10-15 mg/dL than glibenclamide treatment with higher significance (p<0.001). Extract treatment showed better results than standard drug in liver and kidney function test and exhibited its better potential in controlling diabetic complications. Extract treatment increased HDL-C and reduced triglycerides, LDL-C, VLDL-C and TC much better and with higher significance than standard drug. Extract treatment reduced TC by at least 60-80mg/dL (p<0.01) in comparison to caffeine-nicotine-diabetic control group. Extract treatment reduced 10-15mg/dL of more total cholesterol than that of standard drug. Conclusion: Caffeine-nicotine co-administration-induced exaggeration of type 2 diabetes was better treated by CI extract than that of standard drug gibenclamide. Keywords: Type 2 diabetes, Streptozotocin, Caffeine, Nicotine, Diabetic complication, Rat